STRATEGI PENGELOLAAN LINGKUNGAN PADA EKOSISTEM MANGROVE DI SEKITAR MUARA SUNGAI BOGOWONTO KABUPATEN KULONPROGO - , RANI SAWITRI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The southern coast of Kulonprogo District has many estuaries which are potential for habitat of mangrove, ones in Bogowonto River. The aims of this research were to study: (1) The composition of mangrove vegetation in rehabilitation area, (2) Physical environmental factors that support the growth of mangrove and, (3) Management strategy for mangrove ecosystem around estuary of Bogowonto River using ecological approach point of view. The method used was purposive sampling. Vegetation data were collected using quadrate plots of 2 m x 2 m for seedling